Penegakkan Hukum terhadap Pelanggaran HAM di Papua: Diskriminasi Etnis - Muhamad Rangga Musaddad; Alif Muslim; Helmi Mutawalli; Maskumambang Wiratama; Muhamad Adam Auliya Rahman; Lip Hidayat (Mandub : Jurnal Politik, Sosial, Hukum dan Humaniora, 2024)
Racial discrimination and violence against minority communities is prohibited by law, and the protection of minority groups is guaranteed by the Constitution, national laws, as well as international laws or conventions ratified by Indonesia, such as the ICCPR and ICERD. However, cases of violence involving ethnic Papuans are often ignored by the state, even though this is a violation of human rights. This research will use a normative juridical approach by presenting and analyzing the validity of statutory provisions. The socio-legal study in this research will be carried out by analyzing social studies, multidisciplinary social science theories related to the phenomenon of racial discrimination against ethnic Papuans, such as psychology in looking at prejudice and discrimination; Communication Studies; Social Integration and Disintegration Theory; and Social Conflict Theory. The aim of this research is to examine law enforcement using a social science paradigm. This research will review the quality of law enforcement, the extent to which these rules are enforced, and the extent to which law enforcement and the government can fulfill citizens' rights not to be discriminated against. This research shows that discrimination against the Papuan people is caused by racial discrimination in various aspects, including economics, politics, education and law enforcement. The application of anti- discrimination laws must be based on the professionalism of law enforcement officials so as not to give rise to new discrimination in law enforcement. This research recommends that the Indonesian Government increase political will in enforcing anti-discrimination and violence laws in all cases, especially against the Papuan ethnic group. Maximum anti-discrimination law enforcement efforts are needed to realize human rights goals, namely the provision, enforcement and protection of human rights.